Textos y audios digitales, dos medios tecnológicos eficientes para potencializar la competencia lectora (2019)
This research was carried out in order to analyze the efficiency of digital texts and audios at improving reading competence in 6th grade students of the Institución Educativa Técnica Comercial de Ponedera. The methodology was conducted using a quantitative approach, under an empirical-analytical paradigm with a quasi-experimental design of pre-post-test type, with an experimental group (made up of 39 students) exposed to intervention with didactic sequences mediated by digital texts and audios and a control group (made up of 34 students) which developed the same activities but without the assistance of said ICTs. In order to collect the information, questionnaire and tests (pretest-posttest) techniques were used and a parametric statistical analysis was performed applying Pearson's correlation coefficient and linear regression concepts. This allowed to demonstrate that the intervened group improved its reading competence regarding aspects such as: quality, speed and levels of reading comprehension. In addition, it supports that the use of ICTs as a mediating tool in the development of the pedagogical act foster motivation and interest among the students within in the teaching-learning processes generating an active and spontaneous participation environment.